Social support and psychosocial functioning in women after mastectomy. Issue 3 (June 2020) - Janowski, Konrad; Tatala, Małgorzata; Jedynak, Tomasz; Wałachowska, Karolina
Abstract: Objective: Social support has been reported as beneficial for the psychological functioning of people coping with a disease. The objective of this study was to verify whether levels of perceived social support are associated with psychosocial functioning in women who have had a mastectomy and whether specific types of social support are linked to specific indices of functioning. Method: Seventy women with a history of mastectomy completed questionnaires measuring their psychosocial functioning as related to their health status: Disease-Related Appraisal Scale, Acceptance of Life with the Disease Scale and Beck Depression Inventory. All participants also completed a measure of perceived social support (Disease-Related Social Support Scale). Results: Women who reported higher levels of perceived social support revealed statistically significantly lower levels of depressive symptoms, higher appraisals of their disease in terms of challenge and value, and lower appraisals of their disease in terms of obstacle/loss. Women with greater social support also revealed higher levels of acceptance of life with the disease compared to those with less social support. Regression analyses showed that spiritual support was the type of support that significantly accounted for the variance in the majority of functioning indices. Some indices of functioning were also significantly accounted for by emotional and instrumental support. Significance of the results: The process of psychological adjustment to a life-threatening disease such as breast cancer depends on multiple variables; however, social support, including spiritual support, seems to be one significant contributor to this process.